2564 resected periampullary adenocarcinomas at a single institution: trends over three decades. Issue 1 (8th March 2013) - He, Jin; Ahuja, Nita; Makary, Martin A.; Cameron, John L.; Eckhauser, Frederic E.; Choti, Michael A.; Hruban, Ralph H.; Pawlik, Timothy M.; Wolfgang, Christopher L.
Abstract Objective This study was carried out to determine relative survival rates and trends in outcomes in patients who underwent resection of periampullary adenocarcinomas (PACs) with curative intent at a single institution over the last three decades. Methods From 1980 to 2011, 2564 pancreaticoduodenectomies (PDs) were performed for PACs. Pathological diagnosis, therapy and survival were retrospectively analysed. Results The primary sites included the pancreas (66%), ampulla (16%), bile duct (12%) and duodenum (6%). Operation volume increased from 11 per year in the 1980s to 135 per year in the 2000s (P < 0.001). Patients in the 1980s were younger (median age: 64 years; range: 33–90 years) than those in the 1990s (median age: 68 years; range: 31–103 years) and 2000s (median age: 68 years; range: 24–93 years) (P < 0.001). Over time, the frequency of a diagnosis of pancreatic cancer arising from intraductal papillary mucinous neoplasm increased from 2% in the 1980s to 8% in the 2000s (P < 0.001). The rate of 30‐day mortality after surgery in the 1980s was 2%, which was similar to rates in the 1990s (1%) and 2000s (1%). Survival in each type of PAC did not change over time. Pancreatic cancer was associated with the worst survival (median survival: 19 months) compared with adenocarcinomas of the ampulla (median survival: 47 months), bile duct (median survival: 23 months) and duodenum (median survival: 54 months) (P < 0.001). Conclusions There are significant differences among PACs in longterm survival following PD. Although the numbers of patients undergoing safe resection have increased, overall longterm outcomes have not improved significantly.